2011
DOI: 10.1161/hypertensionaha.110.165100
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent Contractions in Hypertension

Abstract: M ost isolated arteries respond to shear stress and several vasodilator substances, as demonstrated first for acetylcholine, 1 by releasing endothelium-derived relaxing factor (or nitric oxide [NO]), and various endothelium-derived hyperpolarizing signals. [2][3][4][5] However, in certain blood vessels, when exposed to stretch, agonists such as thrombin, acetylcholine, and adenosine nucleotides (adenosine diphosphate [ADP] and adenosine triphosphate [ATP]) or calcium ionophores, the endothelium produces diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
132
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 106 publications
17
132
0
2
Order By: Relevance
“…In addition, our studies showed that ACh-mediated vasoconstriction was coupled to the ACh-COX contraction pathway previously described in fish Urriola-Urriola, 2014, 2015). This was similar to that reported in human and rat hypertension models (Vanhoutte et al, 2005;Shi et al, 2008) where there was an endothelium dysfunction because of a lower bioavailability of NO due to the increase in oxidative stress that stimulates COX and production of prostaglandin vasoconstrictors (Vanhoutte, 2011). Therefore, we propose that ectotherm animals such as amphibians could have a similar pattern of vascular response as that described in fish.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, our studies showed that ACh-mediated vasoconstriction was coupled to the ACh-COX contraction pathway previously described in fish Urriola-Urriola, 2014, 2015). This was similar to that reported in human and rat hypertension models (Vanhoutte et al, 2005;Shi et al, 2008) where there was an endothelium dysfunction because of a lower bioavailability of NO due to the increase in oxidative stress that stimulates COX and production of prostaglandin vasoconstrictors (Vanhoutte, 2011). Therefore, we propose that ectotherm animals such as amphibians could have a similar pattern of vascular response as that described in fish.…”
Section: Introductionsupporting
confidence: 89%
“…In mammals, on the other hand, ACh induces vascular smooth muscle relaxation by activation of muscarinic receptors expressed in endothelial cells (Furchgott and Zawadzki, 1980). However, ACh-mediated vasoconstriction suggests that a coupled ACh-COX contraction described in our study in fish is similar to that reported in human hypertension and hypertension rat models (Vanhoutte et al, 2005;Shi et al, 2008) where there was an endothelium dysfunction because of a lower bioavailability of NO due to the increase in oxidative stress that stimulates COX and production of prostaglandin vasoconstrictors (Vanhoutte, 2011).…”
Section: Vascular Response To Acetylcholinesupporting
confidence: 69%
“…However, the latter agent interferes with several other flavoenzyme oxidoreductases, and the former is regarded (at least in Frankfurt) as a nonselective antioxidant that should yield effects comparable with those of ascorbic acid. Similarly, the lovers of the role of thromboxane-prostanoid (TP) receptor activation in COX-mediated endothelial dysfunction 4,5 could argue that it is swept under the carpet of the e-supplemental information with one concentration of a single TP antagonist, without providing data that in the studied preparations under the experimental conditions tested TP antagonism actually is achieved
 It is not surprising that vascular COX produces free radicals during stimulation with acetylcholine. 6 Thus, when viewing the data presented by Virdis et al, 1 one can only bow to the logical conclusion reached that in the human arteries studied COX plays a major role in producing ROS, curtailing the relaxations to acetylcholine solely by reducing the bioavailability of endothelium-derived NO.…”
mentioning
confidence: 99%
“…Furthermore, none of the PRL concentrations modified the basal production of NO in either the presence or the absence of L-NAME (control), confirming that this metabolite does not mediate the vascular effects induced by PRL ( Figure 7C). We therefore hypothesized that PGs and other major vasodilatory agents [48] may mediate the dilatory effect of the hormone. The aortic rings were preincubated for 30 min with INDO prior to precontraction with Phe, followed by the administration of 0.01 nmol/L of PRL.…”
Section: Wwwchinapharcom Gonzalez C Et Almentioning
confidence: 99%